2012
DOI: 10.1007/s10682-012-9622-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetically differentiated races and speciation-with-gene-flow in the sunflower maggot, Strauzia longipennis

Abstract: The ecological interactions parasitic insects have with their hosts may contribute to their prodigious diversity, which is unrivaled among animals. Many insects assumed to be polyphagous generalists have been shown to consist of several differentiated races, each occupying a different host-niche. The sunflower maggot fly, Strauzia longipennis, has long been thought to consist of two or more races due to its substantial intraspecific morphological variation. Here, we use nuclear and mitochondrial markers to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 60 publications
5
26
0
Order By: Relevance
“…AFLPs previously showed several fixed differences between S. longipennis var. longitudinalis and the other two varieties (Forbes et al ., ), and microsatellites in the current study show a similar signal of strong isolation. The concordance between genetic clusters and morphological traits adds further support to the conclusion that the three varieties are real biological units.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…AFLPs previously showed several fixed differences between S. longipennis var. longitudinalis and the other two varieties (Forbes et al ., ), and microsatellites in the current study show a similar signal of strong isolation. The concordance between genetic clusters and morphological traits adds further support to the conclusion that the three varieties are real biological units.…”
Section: Discussionsupporting
confidence: 77%
“…b) and the three varieties of S. longipennis (blue, green, and red clusters) previously identified by Forbes et al . (). Microsatellite data revealed that the morphology of flies in the three S. longipennis varieties does not overlap for male flies.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations